Roles of Lipolytic enzymes in Mycobacterium tuberculosis pathogenesis - Lin, Hong; Xing, Jiayin; Wang, Hui; Wang, Shuxian; Fang, Ren; Li, Xiaotian; Li, Zhaoli; Song, Ningning (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (Mtb) is a bacterial pathogen that can endure for long periods in an infected patient, without causing disease. There are a number of virulence factors that increase its ability to invade the host. One of these factors is lipolytic enzymes, which play an important role in the pathogenic mechanism of Mtb. Bacterial lipolytic enzymes hydrolyze lipids in host cells, thereby releasing free fatty acids that are used as energy sources and building blocks for the synthesis of cell envelopes, in addition to regulating host immune responses. This review summarizes the relevant recent studies that used in vitro and in vivo models of infection, with particular emphasis on the virulence profile of lipolytic enzymes in Mtb. A better understanding of these enzymes will aid the development of new treatment strategies for TB. The recent work done that explored mycobacterial lipolytic enzymes and their involvement in virulence and pathogenicity was highlighted in this study. Lipolytic enzymes are expected to control Mtb and other intracellular pathogenic bacteria by targeting lipid metabolism. They are also potential candidates for the development of novel therapeutic agents.